DASAR-DASAR FILOSOFIS METODE PEMBELAJARAN BAHASA PRANCIS SEBAGAI BAHASA ASING DI INDONESIA - Rahayu, Siti Perdi (Diksi, 2019)
(Title: The Philosophical Foundations of the Learning Method of French as a Foreign Language in Indonesia). The aim of the current study is to describe the philosophical foundations used in learning French as a foreign language in Indonesia, specifically the language learning which refers to the CECR (Cadre Européen Commun de Rérence) or uniformity in learning, teaching and evaluation. This study adapts the  qualitative descriptive method. The data are in the form of features and characteristics of actionnelle approach, pragmatism and analytical linguistic philosophy foundations. Data are taken from sources such as documents including books on actionnelle approach, Echo 1 and Echo 2 books. Data analysis is done by making a comparative description of the characteristics of the actionnelle approach with the implementation of the philosophy of pragmatism education and the philosophy of analytical linguistic education. The findings of this study indicate that: 1) Pragmatism philosophy implies that education at every level must have criteria to be utilized and applied in social life, because students are indeed social actors, 2) Analytical linguistic philosophy has the principle that word meanings are in sentences, meaning of sentences in language , and the meaning of language exists in various life contexts, 3) Actionnelle approach is characterized by action, assimilating students as language users and as social actors who have tasks to do. The existence of the mentioned similarities can lead us to conclude that that the actionnelle approach gained influence from the philosophy of pragmatism and analytical linguistic.           Keywords: actionnelle approach; pragmatism philosophy;  analytical linguistic philosophy.